Anak dari Keluarga Miskin di Perdesaan Rentan Mengalami Perundungan - Herdiana, Dian (YASIN, 2025)
The village is constructed as a harmonious social order, but seen from the perspective of child protection, the existing social structure does not guarantee the protection of children. This provides opportunities for bullying, especially those from poor families. On this basis, this article is intended to analyze the causes and forms of child bullying in poor families that occur in rural areas. This research uses a qualitative research method with a descriptive approach. The results revealed that the low awareness and understanding of the village community regarding bullying and the lack of child protection policy instruments by the village government are the factors causing bullying. Forms of bullying occur verbally, physically, and mentally. The implication is that children from poor families feel excluded from the social environment and should be able to contribute positively to their growth and development.